The effect of plasma components on hemoglobin release test in red blood cells (RBC). Issue 3 (16th March 2017) - Wang, Cai-Li; Liu, Li-Ping; Han, Li-Hong; Su, Yan; Qin, Wen-Bin; Gao, Li-Jun; Gao, Ya-Qiong; Wang, Cui-Feng; Zhang, Xiao-Yan; Yan, Bin; Sun, Gang
ABSTRACT: Electrophoresis release test (ERT) was established by our lab to observe the re-released hemoglobin (Hb) from red blood cells (RBCs) and whole blood. In this study, ERT was performed to study the effects of different plasma components including plasma, serum, albumin, globulin, fibrinogen, glucose, amino acid, vitamin, insulin, hormone, and inorganic ions on re-released Hb from RBC and whole blood samples during ERT. The results showed that plasma, serum, albumin, globulin, compound amino acid, essential amino acid, vitamin C, insulin, hormone, NaCl, KCl, CaCl2, and NaHCO3 − decreased re-released RBC Hb; while glucose, vitamin B1, vitamin B2, and vitamin B12 elevated re-released RBC Hb. The differing effects of various plasma components on re-released Hb of RBC may play a significant role in blood conservation.